Development of the Adolescents' Communicative Culture in the Context of Digitalization of Additional Education - Dedy Achmad Kurniady; David I. Philippov; Aan Komariah; . Sururi; Asep Suryana; Veronica M. Grebennikova; Natalya I. Nikitina; Mikhail E. Kosov; Natalia V. Lazareva; Olesya V. Dudnik (Emerging Science Journal, 2022)
In the era of digitalization of education and economy and the development of artificial intelligence, adolescents appear highly competitive compared with other generations in understanding digital technologies, acquiring expertise, and mastering modern means of communication, which normally causes intergenerational conflicts and the loss of an adult's personal and functional authority. The aim of this research was to develop and test a model for developing adolescents' communicative cultures in an institution of additional education. The research emphasizes the significance of personality-oriented, interactive-communicative, and cultural approaches and conducts a comparative analysis of the sources. Methodologically, the study relies on a quantitative method with primary sources. Besides, the findings of the study contribute to the existing limited stress on the importance of adolescents' communicative cultures from the perspective of the digitalization of additional education. The study finds that the use of digital options in education has reduced social interaction among students. However, the students prefer to use digital methods of learning as they find them more convenient for communication. Therefore, the digital communication culture has high potential in the educational sector. The findings are novel as this study is one of the few recent studies that examined how communicative culture has transformed due to digital means in education. Doi: 10.28991/ESJ-2022-SIED-019 Full Text: PDF